Using AI responsibly - O'Reilly, Tim (O'Reilly Media, Inc., 2024)
Generative AI is incredibly powerful, but it also introduces new risks - for society, as you've no doubt heard in the media - but also for your company and for you as an employee.
Online resource; title from title details screen (O'Reilly, viewed March 3, 2025)
Keywords: Artificial intelligence -- Management; Artificial intelligence -- Moral and ethical aspects; Artificial intelligence -- Risk management; Intelligence artificielle; Gestion; Intelligence artificielle; Aspect moral; Intelligence artificielle; Gestion du risque; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet